Sea Urchin Coelomocytes Specifically Express a Homologue of the Complement Component C3 - Walid Z. Al-Sharif; J. Oriol Sunyer; John D. Lambris; L. Courtney Smith (1998)
Abstract A homologue of complement component C3 (SpC3) has been cloned and sequenced from the purple sea urchin, Strongylocentrotus purpuratus. The preprocessed, deduced protein size is estimated to be 186 kDa with a short leader and two chains, α and β. There are cysteines in conserved positions for interchain disulfide bonding, and there is a conserved thioester site in the α-chain with an associated histidine. There are five consensus N-linked glycosylation sites, and putative cleavage sites for factor I and C3 convertase. Partially purified SpC3 on protein gels shows a nonreduced size of 210 kDa and, under reducing conditions, reveals an α-chain of 130 kDa and a β-chain of 80 kDa. These sizes are larger than the deduced sizes, suggesting that the protein has carbohydrates added to most of the consensus N-linked glycosylation sites. Phylogenetic analysis of SpC3 compared with other members of the thioester protein family, which includes C3, C4, C5, and α2-macroglobulin, shows that SpC3 is the first divergent complement protein, falling at the base of the complement protein clade. Transcripts from the SpC3 gene (Sp064) are 9 kb, and the gene is expressed specifically in coelomocytes, which are the immunocytes in the sea urchin. Genome blots suggest that SpC3 is encoded by a single copy gene per haploid genome. This is the first identification of a complement component in an invertebrate, and suggests homology of the innate immune system within the deuterostome lineage of animals.